PENGGUNAAN WEBSITE APPSHEET SEBAGAI TEMU BALIK ARSIP INAKTIF FOTO DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN PONOROGO - Sitaviana, Silvi; Husna, Jazimatul; Irawati, Yayuk Endang; Indrahti, Sri (UPT Perpustakaan Universitas Semarang, 2023)
Information is an important part of communication between individuals and groups. Information is closely related to archive search. Archive searching is an important part of archive editing because searching allows researchers to find important information in archives. Based on the results of an archive search survey at one of the archival institutions, namely the Ponorogo Regency Library and Archives Service, archive searches are still limited through Microsoft Excel and there are no other innovations. Seeing current technological developments, researchers offer solutions for searching archives through the AppSheet website at the Ponorogo Regency Library and Archives Service. The purpose of this study, among others, is to find out how to use the AppSheet website, use the AppSheet website in related agencies, as well as the advantages and disadvantages of the AppSheet website. The research method in this study is a qualitative method through interviews and observation. The informants in this study were 4 archivists in related agencies. The results of the study show that how to use the AppSheet website consists of 22 steps. How to use the AppSheet website in related agencies include: 1) The features provided are quite easy to use. 2) Retrieval components that are fulfilled include: users, queries, documents, and matching. 3) The description is complete. 4) The retrieval step is quite easy. 5) Available metadata include: processing unit, file number, file number, description of archive information, time period, and amount. 6) Obstacles in the operation of the AppSheet website as a retrieval of inactive photo archives so far not all users can access and cannot be operated offline. 7) The solution for operating the AppSheet website as a retrieval of inactive photo archives is that later users who really need access to these inactive photo archives will be allowed to view them to get information to support their final thesis or assignment. In addition, active photos need to be placed on a flash disk to back up data. 8) There is no comparison with other applications. 9) Criticism and suggestions follow technology and regulatory developments in politics and law and features are added. Disadvantages of the AppSheet website include: users must understand technology and need to share links so that other users can access them. The advantages: increasing efficiency, effectiveness, presentation of information, when it is static it can be accessed by the public. Keywords: Inactive Photo Archive Retrieval, AppSheet Website, Ponorogo District Library and Archives Service.